2011
DOI: 10.1095/biolreprod.110.088187
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Anti-Müllerian Hormone Production in the Cow: A Multiscale Study at Endocrine, Ovarian, Follicular, and Granulosa Cell Levels1

Abstract: Anti-Müllerian hormone (AMH) is an endocrine marker that can help predict superovulatory responses to treatments administered to cows for embryo production. However, the optimal time of the estrous cycle at which a blood test should be performed for a highly reliable prognosis has not yet been established. Moreover, little is known about the regulation of AMH production. To answer these questions, a study was designed to investigate the regulation of AMH production in cows selected for their high or low ovulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
111
2
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(133 citation statements)
references
References 81 publications
(106 reference statements)
17
111
2
3
Order By: Relevance
“…The current study indicated that AMH was expressed as the follicle began to grow at the primary stage, increased during the subsequent development in preantral follicles, and peaked after antrum formation. The patterns are consistent with previous findings in nonprimate [1,2] and primate [10,11] species. However, though similar in size and morphological characteristics, macaque preantral follicles at the same developmental stage appeared to differ in AMH biosynthesis and secretion, as distinguished by AMH immunostaining intensity and AMH concentrations in the culture media.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The current study indicated that AMH was expressed as the follicle began to grow at the primary stage, increased during the subsequent development in preantral follicles, and peaked after antrum formation. The patterns are consistent with previous findings in nonprimate [1,2] and primate [10,11] species. However, though similar in size and morphological characteristics, macaque preantral follicles at the same developmental stage appeared to differ in AMH biosynthesis and secretion, as distinguished by AMH immunostaining intensity and AMH concentrations in the culture media.…”
Section: Discussionsupporting
confidence: 92%
“…AMH messenger RNA (mRNA) and/or protein is detectable in preantral follicles, peaks in antral follicles, and decreases following subsequent follicle growth to the preovulatory stage in rodents [1], domestic animals [2], and Capsule AMH, co-expressed with AMHR2, was produced heterogeneously by preantral follicles in macaques with levels correlated positively with follicle growth and oocyte maturation. AMH may serve as a biomarker for primate follicular development in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…In cattle, circulating AMH concentrations were constant during the 6-to 9-day breeding period prior to ovulation [9]. Another study showed that circulating AMH concentrations followed a specific dynamic profile during the estrus cycle with the highest correlations between the number of ovulations and AMH levels at estrus and after Day 12 of the cycle [17]. In any case, these studies suggest that circulating AMH concentrations are useful for selecting donor cows able to produce large numbers of embryos for an extended period of the cycle.…”
mentioning
confidence: 99%
“…However, we observed no differences in relative abundances of AMH mRNA from the granulosa cells of small (1 to 5 mm) antral follicles of repeat breeder cows compared with control cows. Rico et al (2011) observed no difference in follicular fluid concentrations of AMH from 3 to 5 mm follicles from cows with a high (>15 CL) superovulatory response compared with cows with a low (<10 CL) superovulatory response. This suggests that fertility status influences the production of AMH by bovine granulosa cells more in the later stages of follicular development than the early stages of follicular development.…”
Section: Discussionmentioning
confidence: 62%